Hidrotherapy to Reduce Plasma Glucose among Patients with Diabetes Mellitus at Rsup Fatmawati (A Case Study) - Salsabila, Refaraz Nadira; Sestramita (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2023)
Background: Diabetes mellitus type 2 occur when there is a problem about insulin production in the body, body resistant to the insulin, or the sensitivity of body to insulin decreased. Management of diabetes mellitus type 2 is needed to prevent further complications. Hydrotherapy is a complementary therapy by using water that can reduce plasma glucose levels among patients with diabetes mellitus. Purpose: the purpose of this case study is to determine the effectiveness of hydrotherapy on reducing plasma glucose level among patients with diabetes mellitus type 2. Methods: the type of this case study is descriptive. Data collection conducted through interviews, observation, and documentation. The subjects in this study were 2 patients with diabetes mellitus type 2 from Fatmawati General Hospital. Result: after finished hydrotherapy for 3 days, the patient's plasma glucose levels decreased significantly with an average decrease in subject I was 41,3 mg/dl and subject II was 23,3 mg/dl. Conclusion: researcher recommends hydrotherapy to be carried out by patient with diabetes mellitus type 2.